Is it time for class I recommendation for sodium-glucose cotransporter-2 inhibitors in heart failure with mildly reduced or preserved ejection fraction?: An updated systematic review and meta-analysis - Treewaree, Sukrit; Kulthamrongsri, Narathorn; Owattanapanich, Weerapat; Krittayaphong, Rungroj (Frontiers in Cardiovascular Medicine, 2023)
Background In heart failure with reduced ejection fraction (HFrEF), sodium-glucose cotransporter-2 (SGLT2) inhibitors were demonstrated to lower cardiovascular mortality (CV death) and hospitalization for heart failure (HHF); however, the advantages of SGLT2 inhibitors in heart failure with mildly reduced (HFmrEF) or preserved ejection fraction (HFpEF) are less clear. SGLT2 inhibitors were reported to enhance quality of life (QoL) in HFmrEF or HFpEF patients; however, the findings among studies are inconsistent. Objective To conduct an updated systematic review and meta-analysis of recent data to assess the effect of SGLT2 inhibitors on cardiovascular outcomes and QoL in patients with HFmrEF or HFpEF. Method Three databases were searched for studies that evaluated SGLT2 inhibitors and their effect on cardiovascular outcomes, including CV death, HHF, all-cause death, and the composite outcome of CV death, HHF, and urgent visit for heart failure (HF), and patient QoL (Kansas City Cardiomyopathy Questionnaire [KCCQ] score compared to baseline, and increase in KCCQ score ≥ 5 points) that were published during January 2000–August 2022. The meta-analysis was performed using the inverse variance method and random-effects model. INPLASY registration: INPLASY202290023. Results Sixteen studies (9 recent RCTs) were included, and a total of 16,710 HFmrEF or HFpEF patients were enrolled. SGLT2 inhibitors significantly reduced composite cardiovascular outcome (CV death/HHF/urgent visit for HF; pooled hazard ratio [HR]: 0.80, 95% confidence interval [95%CI]: 0.74–0.86) and HHF alone (HR: 0.74, 95%CI: 0.67–0.82), but there was no significant reduction in CV death alone (HR: 0.93, 95%CI: 0.82–1.05). Benefit of SGLT2 inhibitors for decreasing CV death/HHF was observed across all subgroups, including left ventricular ejection fraction (LVEF) range, diabetes status, New York Heart Association functional class, and baseline renal function. For total HHF, SGLT2 inhibitors conferred benefit in both LVEF 50–60% (HR: 0.64, 95%CI: 0.54–0.76), and LVEF >60% (HR: 0.84, 95%CI: 0.71–0.98). Significant change was observed in the KCCQ-clinical summary score compared to baseline (mean difference: 1.33, 95%CI: 1.31–1.35), and meaningful improvement in QoL was shown across all 3 types of increase in KCCQ score ≥ 5 points. Conclusion This study demonstrates the benefits of SGLT2 inhibitors for improving cardiovascular outcomes and QoL in HFmrEF or HFpEF patients.